Increase in rotavirus prevalence with the emergence of genotype G9P[8] In replacement of genotypeG12P[6] In Sabah, Malaysia - Lia Natasha Amit; Jecelyn Leaslie John; Daisuke Mori; Abraham Zefong Chin; Andau Konodan Mosiun; Kamruddin Ahmed (Springer Nature, 2023)
Rotaviruses are major causative agents of acute diarrhea in children under 5 years of age in Malaysia. However, a rotavirus vaccine has not been included in the national vaccination program. To date, only two studies have been carried out in the state of Sabah, Malaysia, although children in this state are at risk of diarrheal diseases. Previous studies showed that 16%–17% of cases of diarrhea were caused by rotaviruses and that equine-like G3 rotavirus strains are predominant. Because the prevalence of rotaviruses and their genotype distribution vary over time, this study was conducted at four government healthcare facilities from September 2019 through February 2020. Our study revealed that the proportion of rotavirus diarrhea increased significantly to 37.2% (51/137) after the emergence of the G9P[8] genotype in replacement of the G12P[8] genotype. Although equine-like G3P[8] strains remain the predominant rotaviruses circulating among children, the Sabahan G9P[8] strain belonged to lineage VI and was phylogenetically related to strains from other countries. A comparison of the Sabahan G9 strains with the G9 vaccine strains used in the RotaSiil and Rotavac vaccines revealed several mismatches in neutralizing epitopes, indicating that these vaccines might not be effective in Sabahan children. However, a vaccine trial may be necessary to understand the precise effects of vaccination.